2019
DOI: 10.3390/v11110995
|View full text |Cite
|
Sign up to set email alerts
|

Phylodynamic and Phylogeographic Analysis of Hepatitis Delta Virus Genotype 3 Isolated in South America

Abstract: The hepatitis delta virus (HDV) is a globally distributed agent, and its genetic variability allows for it to be organized into eight genotypes with different geographic distributions. In South America, genotype 3 (HDV-3) is frequently isolated and responsible for the most severe form of infection. The objective of this study was to evaluate the evolutionary and epidemiological dynamics of HDV-3 over the years and to describe its distribution throughout this continent in an evolutionary perspective. While usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
2
8
1
Order By: Relevance
“…HDV genotypes 1 and 3 were detected in PWUDs. The predominance of genotype 3 is consistent with the findings of epidemiological studies in South America, and the identification of HDV genotype 1 reinforces the perspective of its worldwide distribution [30][31][32]. The co-infection of HDV genotype 3 and HBV genotype A (A1 or A2) observed in most PWUDs is also consistent with the studies of people residing in the Brazilian states of Acre, Amazonas, and Pará, and it reinforces the regional pattern of this co-infection [49,93,94].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…HDV genotypes 1 and 3 were detected in PWUDs. The predominance of genotype 3 is consistent with the findings of epidemiological studies in South America, and the identification of HDV genotype 1 reinforces the perspective of its worldwide distribution [30][31][32]. The co-infection of HDV genotype 3 and HBV genotype A (A1 or A2) observed in most PWUDs is also consistent with the studies of people residing in the Brazilian states of Acre, Amazonas, and Pará, and it reinforces the regional pattern of this co-infection [49,93,94].…”
Section: Discussionsupporting
confidence: 86%
“…Based on phylogenetic analyses, it has been classified into eight genotypes (1–8) [ 27 ]. HDV genotypes 1, 3, and 8 are found in South America, with genotype 3 considered to be original and prevalent in the Amazon region [ 29 , 30 , 31 , 32 , 33 ]. HDV infection is often associated with severe liver disease [ 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the available HDV sequences make it possible to reconstruct the history of the evolution of HDV over the past decades, with a rather small 95% HPD, which is very important for understanding viral circulation against the background of HBV vaccination. Thus, using Bayesian analysis, Nogueira-Lima et al demonstrated a decrease in the epidemiological levels of HDV-3 in South America after the introduction of HBV vaccination and donor screening [ 41 ]. Interestingly, our data on HDV epidemiological dynamics in Yakutia do not indicate any stable decrease after the implementation of newborn HBV vaccination in 1998, either in the effective number of infections or in the reproduction number.…”
Section: Discussionmentioning
confidence: 99%
“…4 Copyright 2006, Instituto Nacional de Salud, covered under CC BY‐NC. (B) Prevalence of HBV in native population of the Amazon younger than 5 years, 2009 3 . Adapted with permission from Revista Peruana de Medicina Experimental y Salud Pública 6 .…”
Section: Hbv and Hdv Infection In Peruvian Amazoniamentioning
confidence: 99%
“…An atypical form of delta hepatitis was initially described in Brazil, where it was named “Lábrea fever” because it predominated in the city of Lábrea in the Alto Purus region. Subsequently, Lábrea fever was described in areas of the Amazon rainforest located in Peru, Colombia (Santa Marta), and Venezuela 3 . First described in young individuals, this peculiar fulminant hepatitis has a high fatality rate and unique histological picture, with moderate hepatocellular necrosis, hepatocellular ballooning, and enlarged hepatocytes containing cytoplasmic drops of fat surrounding the nucleus.…”
mentioning
confidence: 99%